Impact of Nurse's Satisfaction on Work Performance - Dara Abdulla Al-Banna (Hawler Medical University, 2018)
Background and objective: A high satisfaction of nurses imply an improvement in effectiveness and performance in doing work or healthcare service. This study aimed to find out the relationship between nurse's job satisfaction and their work performance in the hospital while providing health care. Methods: A descriptive cross-sectional study was carried out at both Hawler and Rizgary Teaching Hospitals in Erbil City of the Kurdistan Region of Iraq. A randomized-clustered sampling technique was used for enrolling 89 nurses and 27 their team-leaders through a direct interview by a questionnaire to assess nurse's job satisfaction by researcher and evaluate work performance by their team leaders. The outcome focused on the correlation coefficient to find out the correlation between job satisfaction and work performance of nurses. Results: The majority of the study sample was between 20 and 32 years old, Institute graduated, had fewer than five years of experience, and single among nurses with 33 and 45 years old, college graduated, more than five years, and married among team-leaders, from urban areas of both groups. Most of the nurses had fairly job satisfaction and team-leaders think that the nurses need some improvement in their work performance. Conclusion: There was a strong positive correlation between nurse's job satisfaction and their work performance in the hospital during providing health care.